Toba Highland Peatlands: Exploring a Unique Ecosystem and its Environmental Significance - Minasny, Budiman; Sabrina, Tengku; Akoeb, Erwin Nya (Journal of Smart Agriculture and Environmental Technology, 2023)
This paper provides a review of the Toba highland peatlands, focusing on their characteristics, environmental impacts and historical significance. The Toba area was influenced by a super volcano eruption around 74,000 years ago, which resulted in global cooling and the deposition of pyroclastic materials known as the Youngest Toba Tuff. The peatlands in the region formed south of the caldera and are characterised by varying extents and thicknesses. Radiocarbon dating indicates that the peat in Toba highland is approximately 20,000-30,000 years old, making it a valuable carbon stock and a record of the past. However, the drainage of peatlands has led to significant environmental degradation. It has resulted in increased CO2 emissions, reduced water supply for local farmers, loss of biodiversity, air pollution from open fire burning practices, and an increased fire hazard. Understanding the environmental impacts and historical significance of Toba highland peatlands is crucial for conservation efforts and sustainable land management practices.